Scalable Notch Antenna System for Multiport Applications - Abdurrahim Toktas (International Journal of Antennas and Propagation)
A novel and compact scalable antenna system is designed for multiport applications. The basic design is built on a square patch with an electrical size of 0.82λ0×0.82λ0 (at 2.4 GHz) on a dielectric substrate. The design consists of four symmetrical and orthogonal triangular notches with circular feeding slots at the corners of the common patch. The 4-port antenna can be simply rearranged to 8-port and 12-port systems. The operating band of the system can be tuned by scaling (S) the size of the system while fixing the thickness of the substrate. The antenna system with S: 1/1 in size of 103.5×103.5 mm2 operates at the frequency band of 2.3–3.0 GHz. By scaling the antenna with S: 1/2.3, a system of 45×45 mm2 is achieved, and thus the operating band is tuned to 4.7–6.1 GHz with the same scattering characteristic. A parametric study is also conducted to investigate the effects of changing the notch dimensions. The performance of the antenna is verified in terms of the antenna characteristics as well as diversity and multiplexing parameters. The antenna system can be tuned by scaling so that it is applicable to the multiport WLAN, WIMAX, and LTE devices with port upgradability.